Correlation between First and Second Trimester Uterine Artery Doppler Velocimetry and Placental Bed Histopathology. (13th July 2014) - Akbaş, Murat; Şen, Cihat; Calay, Zerrin
Abstract : Aim . To evaluate the relationship between uterine artery Doppler indices and placental bed histopathology independent of clinical outcome. Materials and Methods . Uterine artery measurements were performed to 510 pregnant women who had come for routine antenatal care in 11–14th and 20–24th weeks. Placental bed biopsies from 141 cases were taken during cesarean section. Physiological changes and abnormal placental histology findings were investigated and compared with Doppler findings. Results . 116 biopsies were accepted as adequate biopsy and included in the study. Physiological changes were seen in 100 biopsies. Statistically significant higher PI and RI values in second trimester and higher notch rate in both trimesters were detected in the abnormal placental histology group (P < 0, 001 ). Conclusion . Strong relationship between uterine artery Doppler indices and preeclampsia or intrauterine growth retardation has been shown in previous studies. In our study, we concluded that there is significant relationship between Doppler findings and placental bed histopathology independent of clinical course.